Maturity Level of ITSM Analysis Using ITIL V3 Framework in State Electricity Enterprise Purwokerto - Setyadi, Resad; Priyatiningsih, Enggar (JUITA: Jurnal Informatika, 2021)
In the industrialized world, information technology has become an essential component that everyone can feel and use. However, IT's proper use can provide opportunities for increased productivity and effective and efficient company processes. The quality of the service supplied is related to managing the problems faced and handling its day-to-day service operations. The purpose of this research is to analyze the IT service management (ITSM) of the National Electricity Company (NEC) in Purwokerto with media analysis using the Information Technology Infrastructure Library (ITIL) v3 framework. The method used is a quantitative method with observation, distribution of questionnaires, and data analysis as a follow-up. Maturity level analysis becomes the target of assessment to become a reference for providing recommendations for the performance of ITSM. The results of the maturity level show that NEC Purwokerto is at the optimal level. The advice given is that NEC Purwokerto maintains IT services' performance so that the NEC Purwokerto company's business strategy continues to run well and improve